Early Chagas’ heart disease in the Ecuadorian Amazon. Treatment and outcome of a clinical case - Amunárriz, Manuel (Revista Universidad de Guayaquil, 2013)
Objective: This is a case of early chagasic heart disease in a 9-year-old boy, identified by the initials JCV, with the evolution of the condition after the treatment was established. Methods: The methods employed in the diagnosis and monitoring of this case are set out as follows: basic laboratory, chest X-rays with the cardiothoracic index, electrocardiogram and determination of the PR and of the QTcintervals and echocardiograms and ELISA tests to determine chagasic antibody levels. The therapeutic criteria are outlined, with Nifurtimox: 12 milligrams per kilo a day for a time period of 120 days, and supportive therapies. Results: The results obtained over the successive stages of the condition are described. Within a period of four months, the cardiothoracic index became normal; the first-degree atrioventricular block disappeared; alterations in the ventricular repolarisation returned to normal values; antibody titers detected by ELISA tests went below the cut-off point. Conclusions: A good result was observed with the established therapy with Nifurtimox, without adverse reactions in the patient. The data obtained suggest the existence of childhood chagasic heart disease of recent origin, with full recovery likely. The patient needs to be monitored at both immunological and echocardiographic levels over a long time period in order to confirm the results obtained.